Phisycal Quality Analysis of Red Guava (Psidium guajava L.) Using Edible Coating of Carrageenan and Glycerol - Dian Karuniasari; Dian Purbasari (Protech Biosystems Journal, 2022)
Red guava (Psidium guajava L.) is one of the crop commodities inIndonesia. Red guava (Psidium guajava L.) belongs to the climataryric fruit groupthat has high respiration and ripens through an increase in CO2 and ethylene.Climateric fruits have a fairly short shelf life that can accelerate the fruit to bedamaged or decayed. Decay in the red guava fruit (Psidium guajava L.) occurs dueto the rapid respiration process due to poor postharvest handling. Decay on the fruitcan be reduced by applying post-harvest technology, one of which is by coating thesurface skin of the fruit using the edible coating method. Edible coating can bedone using the base material of carrageenan and glycerol. The purpose of this studyis to determine the physical quality of red guava fruit and the effect of ediblecoating from carrageenan and glycerol on red guava fruit. The physical qualities ofthe red guava fruit analyzed were color, shrinkage weight and texture. The resultsshowed the smallest brightness level (L) value of 52.18, the smallest reddish level(a) value of -15.91, the smallest yellowish level (b) value of 35.14, the smallestweight shrinkage value of 28.45% and the smallest texture value of 0.00180 mm /gram.second on the 10th day, namely guava with 1.5% carrageenan treatment and2% glycerol.